2018
DOI: 10.4094/chnr.2018.24.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Properties of Self-Report Questionnaires Measuring the Social Adjustment for Youth after Treatment of Childhood Cancer: Systematic Review

Abstract: The purpose of this study was to evaluate measurement properties of self-report questionnaires measuring the social adjustment for youth after treatment of childhood cancer. Methods: Social adjustment measurement tools were identified through a two-stage systematic review. First, we searched for articles using self-report questionnaires to measure the social adjustment of youth after the treatment of childhood cancer. The appropriate tools were listed and categorized. Second, using methodological filters, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Childhood and adolescent cancer survivors (CACS) experience various neurological and cognitive complications including physical weakness, developmental disabilities, stunted growth, and fears of post-treatment recurrence. Consequently, it has also been reported that they have trouble with regular school attendance and experience various obstacles to participating in activities, decreased self-esteem, and confusion about self-identity [2,[4][5][6][7][8][9][10][11][12][13][14][15]. In addition, previous studies on the needs of CACS found that many of them had unmet needs re- lated to continuing health management, healthy living and self-actualization, emotional well-being, social interaction, academic performance and future careers [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood and adolescent cancer survivors (CACS) experience various neurological and cognitive complications including physical weakness, developmental disabilities, stunted growth, and fears of post-treatment recurrence. Consequently, it has also been reported that they have trouble with regular school attendance and experience various obstacles to participating in activities, decreased self-esteem, and confusion about self-identity [2,[4][5][6][7][8][9][10][11][12][13][14][15]. In addition, previous studies on the needs of CACS found that many of them had unmet needs re- lated to continuing health management, healthy living and self-actualization, emotional well-being, social interaction, academic performance and future careers [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Research on CACS in Korea published in the past 10 years mainly consists of surveys related to the health needs of CACS [2,5,7,8,[10][11][12][13][14][15], systematic reviews [16], and qualitative research studies [6,9,17]. However, these studies only address specific topics related to CACS.…”
Section: Introductionmentioning
confidence: 99%